Modeling infiltration rates in a saturated/unsaturated soil under the free draining condition - Herrada, Miguel A.; Gutiérrez-Martin, Alfonso; Montanero, José M. (Journal of hydrology (Amsterdam), 2014)
•We propose a model to simulate infiltration into heterogeneous soils.•The model was validated by studying the water flow in a homogeneous soil.•The model predicts the surface runoff for both homogeneous and stratified soils. We propose a model to simulate infiltration into heterogeneous soils, with arbitrary initial water content distributions, subject to unsteady rainfall, and under the free draining condition. It is a mass conservative theoretical approach based on the numerical resolution of the one-dimensional Richards equation. The model tracks the movement of the wetting front along the soil profile, checks the ponding status, and handles the shift between ponding and non-ponding conditions in the course of the simulation. It partitions the rainfall input into infiltration and surface runoff whenever the upper soil layer is saturated. We validate our theoretical approach by comparing the results for a homogeneous soil under steady rainfall with those calculated with Chemflo-2000. The differences between our approach and the modified Green-Ampt model are showed by considering the infiltration under unsteady rainfall conditions. Finally, we illustrate the model capabilities by examining the water flow and surface runoff for both homogeneous and stratified soils under intense rainfall events.